Indirect evaluation of digestive tract function on male lambs and ram based on feed digestibility and eating behavior - Prima, A.; Rianto, E.; Purbowati, E.; Purnomoadi, A. (Diponegoro University, 2018)
This studywasaimed to examine the development and function ofdigestive organsof lamb in digesting feed based on feed digestibility valueandeating behaviour. The materials used were 11 lambs aged 3-4 months, body weight(BW)14.78 ± 1.99 kg (CV 3.98%), and 11 ramsaged 10-12 months, BW 22.18 ± 1.81 kg (CV 3.29%). The study used a completelyrandomized design of 2x2 in nestedpatterns. There were two ages compared (lambs vs ram) and every age was nested the diet i.e.100%Napiergrass (G100) vs mixed pellet 50% grass and 50% concentrate(G50C50). The diet was given at 3.5% of BW. Parameters observed were dry matter intake(DMI)and digestibility, eating and ruminating time. The results showed that were no significant differences between lambs and rams in DMI (averaged 3.33% BW),digestibility (averaged 49.00%), eating (192.56 min/d), and ruminating (364 min/d). Animalsgiven diet G50C50 had higher (P<0.05) DMI (666 vs 565 g/d), digestibility (50.49%vs 47.53%), and less (P<0.05) eating (47 vs 338 min/d) and ruminating (305 vs 423 min/d), as compared withthose fed diet G100.It is concludedthat the digestive tracts of lambs had developed and function to the stage similar to ram.